Possibility of applying international AACSB accreditation standards in the faculties of business and Economics- case study in the college of management and Economics-University of Baghdad - سعيد سناء عبد الرحيم; محمد مصطفى مهند (Journal of Economics and Administrative Sciences, 2017)
Attention increased to the topic of academic accreditation by the university as a modern philosophy by which to improve its performance and provide high-quality education. Universities and colleges in general and Iraqi universities and colleges in particular have begun interest in accreditation and desire to get it. So starting from the pursuit of the Administration and Economics College / Baghdad University in obtaining accreditation of Association to Advance Collegiate Schools of Business (AACSB) The research is present which aims to determine the level of application (AACSB) International standards at the College of Administration and Economics / Baghdad University in preparation to get its accreditation in the future. Research adopted case study method were data on the status of the application (AACSB) standards was collected through the use of checklists, which have been prepared according to the (AACSB) international standards . This requires interviews with faculty members and accreditation committee members, as well as field cohabitation of researcher at the college in order to get the required data. The results indicated that (curriculum content) standard and (degree program educational level, structure and equivalence) standard, has achieved the highest rate in application and documentation .and the standard of (executive education) has less rate of the application and documentation. Accordingly, the research recommends that to establish a special office of executive education along the lines of consultancy office or attachable to it, offers a Special education programs of leaders and executives of public and private sectors in return for cash.